``Why do I Honor and Love Father Masaryk?'' On the Way Children's Sections of Newspapers in Interwar Czechoslovakia Formed the Image of T. G. Masaryk - Case Studies of Nasim Detem and Tribuna Mladeze - Klaban, Terry (Bohemica Olomucensia, 2025)
The study presents how the first president of Czechoslovakia, T. G. Masaryk, was portrayed in daily newspapers' Sunday sections for children in the interwar period. By comparing two diverse periodicals - Nasim detem from Nase politika and Tribuna mladeze from Tribuna - the author shows how these sections depicted Masaryk as a fatherly and self-sacrificing figure, as well as a leader and a liberator of the nation. In addition, they used similar motifs and narratives, for example, emphasizing his simple origins, his hard work and devotion to the country. Masaryk was presented as a role model for young readers, with the objective of fostering civic engagement and cultivating a sense of national identity. This comparison underscores the ideological function of children's media during the First Czechoslovak Republic and reveals how these portrayals mobilised emotional language and child-centric perspectives to promote loyalty, moral values, and national pride. It demonstrates that, even in newspapers without explicit political affiliations, Masaryk's image was used to promote civic education
Keywords: T. G. Masaryk; Nasim detem; Tribuna mladeze; children's newspaper sections; ideology